Interpersonal Problems, Dependency, and Self‐Criticism in Major Depressive Disorder. Issue 1 (3rd October 2014) - Dinger, Ulrike; Barrett, Marna S.; Zimmermann, Johannes; Schauenburg, Henning; Wright, Aidan G. C.; Renner, Fritz; Zilcha‐Mano, Sigal; Barber, Jacques P.
<x xml:space="preserve">Abstract</x> Objectives The goal of the present research was the examination of overlap between 2 research traditions on interpersonal personality traits in major depression. We hypothesized that Blatt's (2004) dimensions of depressive experiences around the dimensions of relatedness (i.e., dependency) and self‐definition (i.e., self‐criticism) are associated with specific interpersonal problems according to the interpersonal circumplex model (Leary, 1957). In addition, we examined correlations of interpersonal characteristics with depression severity. Method Analyses were conducted on 283 patients with major depressive disorder combined from 2 samples. Of the patients, 151 participated in a randomized controlled trial in the United States, and 132 patients were recruited in an inpatient unit in Germany. Patients completed measures of symptomatic distress, interpersonal problems, and depressive experiences. Results Dependency was associated with more interpersonal problems related to low dominance and high affiliation, while self‐criticism was associated with more interpersonal problems related to low affiliation. These associations were independent of depression severity. Self‐criticism showed high overlap with cognitive symptoms of depression. Conclusion The findings support the interpersonal nature of Blatt's dimensions of depressive experiences. Self‐criticism is associated with being too distant or cold toward others as well as greater depression severity, but is not related to the dimension of dominance.